2020
DOI: 10.1159/000512470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bandage Contact Lenses versus Eye Patching in Early Postoperative Period of Müller’s Muscle-Conjunctival Resection

Abstract: Purpose: Patients with blepharoptosis who are treated with Müller’s muscle-conjunctival resection (MMCR) may experience postoperative pain and discomfort related to the suture material on the palpebral conjunctiva. This study aims to compare the postoperative subjective complaints, such as pain and discomfort, with a visual analog scale (VAS), and objectively evaluate the cornea with a tear break-up time (TBUT) test and fluorescein staining following MMCR that was managed by either a bandage contact lens (BCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nevertheless, a study has demonstrated that proper BCL administration after cataract surgery also contributes to the successful management of dry eye following cataract surgery [ 12 ]. Some studies have also shown that the application of BCL after pterygium excision or Müller's muscle-conjunctival resection seems effective in reducing postoperative pain and eye-stinging [ 7 9 ]. Our study confirms that HPMC and BCLs can be safely used in the perioperative phase of cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a study has demonstrated that proper BCL administration after cataract surgery also contributes to the successful management of dry eye following cataract surgery [ 12 ]. Some studies have also shown that the application of BCL after pterygium excision or Müller's muscle-conjunctival resection seems effective in reducing postoperative pain and eye-stinging [ 7 9 ]. Our study confirms that HPMC and BCLs can be safely used in the perioperative phase of cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Terapeutic bandage contact lenses (BCLs) have been widely used in various ocular conditions related to corneal epithelial injury repair. Tey have also been shown to relieve discomfort and promote wound healing after cataract surgery [7][8][9][10]. However, some studies have indicated that the use of BCLs may cause some degree of ocular surface infammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative use of a protective bandage lens can help safeguard the cornea following ocular surface surgery [ 23 , 24 ]. Bandaged soft contact lenses are commonly used in surface ablation surgery to promote epithelial healing, reduce pain, and prevent corneal haze formation [ 25 ,][26]].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that BCLs can quickly alleviate excruciating ocular pain and provide binocular vision after the onset of a corneal abrasion ( 11 ), and BCLs are now a preferred treatment option for many other ocular complications and surgeries including postoperative Muller's Muscle-Conjunctival Resection ( 12 ). Mechanistically, the bandage contact lens protects against friction of the eyelid and air and provides a structure for re-epithelialization and, therefore, healing.…”
Section: Application Processmentioning
confidence: 99%